The nature and extent of sexual assault in the sky: Shining a light on a ‘black box’ - Mancini, Christina (International review of victimology, 2023)
Strikingly, federal data sources tracking the nature and extent of sexual assaults that occur aboard airlines are incomplete and typically not released to the public. In order to better understand this relatively hidden social phenomenon, we conducted a content analysis of media reports published over approximately a 20-year period (2000–2020). Within these media reports, we analyzed the incident characteristics of in-flight sexual assaults, reporting behaviors of victims, airline responses to victimization, and criminal justice processes such as adjudication. Findings reveal certain patterns in the coverage concerning victim and perpetrator characteristics, offense characteristics, flight information, and post-offense outcomes. In synthesizing study results, we apply tenets of routine activities theory (RAT) and the #MeToo perspective. We outline implications for future study and policy.